Konsep Dasar Career Exploration dalam Perspektif Teori Holland (SCHOULID: Indonesian Journal of School Counseling, 2021)
One of the most important factors in a teenager's life is career exploration. Career is a choice of work that is a goal for an individual or can be interpreted as the development of a person's life journey. Career planning that is mature will be greatly influenced by the results of career exploration carried out by adolescents. Because in career exploration, teenagers carry out career tracking activities in a planned and systematic way towards what they are interested in and what suits their talents. Career exploration in the perspective of Holland's theory is how individual and environmental characteristics lead to career choices. There are six types of environment according to Holland's theory, namely Realistic, Investigative, Aristic, Social, Active and Conventional. This article uses a literature review research method. Literature review is a library research that is obtained through searching various books, journals and other publications that can support the research topic.